2023
DOI: 10.3389/fmicb.2023.1131860
|View full text |Cite
|
Sign up to set email alerts
|

Role of two RpoN in Bradyrhizobium sp. strain DOA9 in symbiosis and free-living growth

Abstract: RpoN is an alternative sigma factor (sigma 54) that recruits the core RNA polymerase to promoters of genes. In bacteria, RpoN has diverse physiological functions. In rhizobia, RpoN plays a key role in the transcription of nitrogen fixation (nif) genes. The Bradyrhizobium sp. DOA9 strain contains a chromosomal (c) and plasmid (p) encoded RpoN protein. We used single and double rpoN mutants and reporter strains to investigate the role of the two RpoN proteins under free-living and symbiotic conditions. We observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…In the previous work, we demonstrated that the regulatory RpoN is required to express other nitrogen-fixing genes under free-living and symbiotic conditions. Moreover, the study on the deletion of rpoN genes in DOA9 suggested an alternative sigma factor affecting colony morphology characteristics, leading to differences in its performance in nitrogen-fixing nodule phenotypes, as described by Wongdee et al ( 13 ).…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…In the previous work, we demonstrated that the regulatory RpoN is required to express other nitrogen-fixing genes under free-living and symbiotic conditions. Moreover, the study on the deletion of rpoN genes in DOA9 suggested an alternative sigma factor affecting colony morphology characteristics, leading to differences in its performance in nitrogen-fixing nodule phenotypes, as described by Wongdee et al ( 13 ).…”
Section: Discussionmentioning
confidence: 88%
“…To confirm the effect of the RpoN mutation on the colony size of strain DOA9 ( 13 ), single colonies from both the DOA9WT and DOA9∆ rpoN mutant strains were examined on a yeast extract-mannitol (YEM) agar plate. The mutant strains were smaller ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, M. japonicum exhibits a broad legume host range, whereas some other mesorhizobia, as is typical of Mesorhizobium huakuii strains, have a narrow host range. Within the family Bradyrhizobiaceae , one broad host range strain that has been well characterized in recent years is of particular interest to us (Teamtisong et al ., 2014; Songwattana et al ., 2017; Wongdee et al ., 2023). Bradyrhizobium sp.…”
Section: Introductionmentioning
confidence: 99%